The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/jor.1100170605
|View full text |Cite
|
Sign up to set email alerts
|

Hamstrings cocontraction reduces internal rotation, anterior translation, and anterior cruciate ligament load in weight‐bearing flexion

Abstract: Strengthening of the hamstrings is often recommended following injury and reconstruction of the anterior cruciate ligament. It has been suggested that hamstrings activity stabilizes the knee and reduces anterior cruciate ligament load during weight-bearing flexion; however, the effects of hamstrings cocontraction on the kinematics and mechanics of the normal knee have not been assessed at physiological load levels. The aim of this study was to determine whether the addition of hamstrings force affects knee rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 16 publications
(14 reference statements)
6
103
1
2
Order By: Relevance
“…sartorius and gracilis) (Buchanan and Lloyd, 1997) only contribute 5.5% to an opposing varus moment (Lloyd and Buchanan, 2001). In addition, hamstring-quadriceps cocontraction only influences anterior tibial shear forces and internal rotation during weightbearing (MacWilliams et al, 1999). Therefore, BF is classified as a specific joint stabiliser that opposes hip extension, and more importantly, valgus loads.…”
Section: Musclementioning
confidence: 99%
“…sartorius and gracilis) (Buchanan and Lloyd, 1997) only contribute 5.5% to an opposing varus moment (Lloyd and Buchanan, 2001). In addition, hamstring-quadriceps cocontraction only influences anterior tibial shear forces and internal rotation during weightbearing (MacWilliams et al, 1999). Therefore, BF is classified as a specific joint stabiliser that opposes hip extension, and more importantly, valgus loads.…”
Section: Musclementioning
confidence: 99%
“…We believe this may be because Walker et al [22] did not load their specimens in a manner consistent with actual gait. When the knee is loaded, these coupled motions have been shown to disappear [23].…”
Section: Studies Free From Skin Movement Artifactmentioning
confidence: 99%
“…Previous cadaver-based knee simulator studies that did not apply hip flexor and ankle plantarflexor torques when modeling stance [15,[29][30][31][32] may have reported greater than physiologically reasonable knee extensor force magnitudes. Torques applied to the hinge knee when modeling stance phase of gait were derived from test subjects in two-legged squat.…”
Section: Discussionmentioning
confidence: 95%
“…Using a cadaver model of stance, MacWilliams et al reported that the addition of hamstrings cocontraction load equal to 30% of body weight load required a 100% increase in knee extension force in stance [29]. Applying hamstrings cocontraction in the hinge knee model resulted in an increase of knee extensor force at all knee flexion angles, albeit not as large as that reported by MacWilliams et al The combined effect of hip and ankle torques along with hamstrings cocontraction resulted in an overall decrease in knee extensor force, and a change from an almost linear relationship with KFA to a curvilinear relationship depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%